2018
DOI: 10.1016/j.jconrel.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

PAMAM dendrimers: blood-brain barrier transport and neuronal uptake after focal brain ischemia

Abstract: Drug delivery to the central nervous system is restricted by the blood-brain barrier (BBB). However, with the onset of stroke, the BBB becomes leaky, providing a window of opportunity to passively target the brain. Here, cationic poly(amido amine) (PAMAM) dendrimers of different generations were functionalized with poly(ethylene glycol) (PEG) to reduce cytotoxicity and prolong blood circulation half-life, aiming for a safe in vivo drug delivery system in a stroke scenario. Rhodamine B isothiocyanate (RITC) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 71 publications
0
58
0
Order By: Relevance
“…The most used DD is poly-amidoamine (PAMAM), which is water soluble and can encapsulate hydrophobe compounds. For example, cationic PAMAM DDs of different generations are used with PEGylation, as a safe in vivo drug delivery system in stroke patients [104].…”
Section: Nanocarriers Nanoparticles and Vectorsmentioning
confidence: 99%
“…The most used DD is poly-amidoamine (PAMAM), which is water soluble and can encapsulate hydrophobe compounds. For example, cationic PAMAM DDs of different generations are used with PEGylation, as a safe in vivo drug delivery system in stroke patients [104].…”
Section: Nanocarriers Nanoparticles and Vectorsmentioning
confidence: 99%
“…There are a wide range of different dendrimer families with great potential for gene delivery, drug delivery, and magnetic resonance and computed tomography imaging [73,74,[82][83][84]. Among them, the most explored dendrimers as delivery vectors for CNS applications have been the poly(amido amine) (PAMAM) dendrimers [80,85,86], but others, like poly(propylene imine) (PPI) [80,[87][88][89][90], poly(ether)-copoly(ester) (PEPE) [91], poly(l-lysine) based (PLL) [92], carbosilane [93], phosphorus [94], and poly(ether imine) (PETIM) [77,95], have also been reported.…”
Section: Dendrimer-based Nanosystemsmentioning
confidence: 99%
“…Under pathological conditions, as, for example, in stroke, traumatic brain injury, multiple sclerosis, AD and brain tumors, the BBB undergoes significant changes [184,191,192]. As the BBB suffers a disruption caused by tight junction disassembly, this can be seen as a window of opportunity for therapeutic NP delivery through paracellular diffusion [86,193].…”
Section: Blood-brain Barriermentioning
confidence: 99%
“…91 In particular, it was shown that PEGylation improved the biocompatibility and reduced the clearance of polyamidoamine (PAMAM) dendrimers. 92 Some studies had applied strategies comparable to micelles to improve cell uptake of dendrimers and consequent gene transfection. One study had conjugated dexamethasone as the targeting device, while another had incorporated reducible residues to dendritic polymers for increased degradability.…”
Section: Dendrimersmentioning
confidence: 99%